2010
DOI: 10.4049/jimmunol.0903654
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cigarette Smoke Exposure Primes NK Cell Activation in a Mouse Model of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a debilitating, progressive lung disease punctuated by exacerbations of symptoms. COPD exacerbations are most often associated with viral infections, and exposure to cigarette smoke (CS) followed by viral infection has been shown experimentally to enhance lung inflammation, tissue destruction, and airway fibrosis. Despite this, however, the cellular mechanisms responsible for this effect are unknown. In this study, we examined NK cell function in a mouse model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 58 publications
3
64
0
Order By: Relevance
“…Although we found that CSE attenuates the influenza-induced innate antiviral response in our human model, as other observations from human cells (25)(26), there are some data suggesting that CS exposure selectively enhances viral-induced pulmonary innate responses in mice (16,27). Influenza virus is not a natural pathogen of mice and requires several passages through them to become mouse adapted and cause disease.…”
Section: Discussionmentioning
confidence: 49%
“…Although we found that CSE attenuates the influenza-induced innate antiviral response in our human model, as other observations from human cells (25)(26), there are some data suggesting that CS exposure selectively enhances viral-induced pulmonary innate responses in mice (16,27). Influenza virus is not a natural pathogen of mice and requires several passages through them to become mouse adapted and cause disease.…”
Section: Discussionmentioning
confidence: 49%
“…These clinical findings suggest that the interactions between CS exposure and viral infections play important roles in clinical scenarios that include virus-induced COPD exacerbations, which have become important clinical parameters in understanding the pathogenesis of COPD. Studies from our laboratory and others have demonstrated that CS and viruses interact in a manner to induce exaggerated inflammatory, emphysema-like, and airway fibrotic changes in animal CS exposure and infection models (11)(12)(13)(14)(15). Studying the mechanisms of how CS exposure and viral infections interact in the lung and affect these pulmonary tissue changes will provide potentially important therapeutic target for diseases such as COPD.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that CS and viruses interact in a manner to induce exaggerated pulmonary inflammation and accelerated emphysema and airway fibrosis (11). However, although almost all of these studies focused on the innate immune mechanisms (11)(12)(13)(14), the possibility that other signaling pathways could also contribute to these effects has not been fully addressed. IL-15 is a proinflammatory cytokine that is expressed by epithelial cells and antigen-presenting cells (APCs), including macrophages and dendritic cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations